2446. Clinical Spectrum and Outcomes of Colistin-Resistant Carbapenem-Resistant Enterobacteriaceae. (26th November 2018) - Ahmed, Sara; Mahmood, Syed Faisal; Sharif, Fatima; Aijaz, Mariam; Awan, Safia; Jamil, Bushra
Abstract: Background: Colistin is considered as one of the last resort of antibiotics against carbapenem-resistant enterobacteriaceae. During the last decade, increased use of colistin or polymyxins due to the increasing prevalence of carbapenem-resistant Gram-negative bacteria has unfortunately led to the emergence of colistin-resistant strains. There are no defined antibiotic regimens for colistin-resistant strains which makes the treatment of these organisms extremely challenging. We therefore report the clinical spectrum and outcomes of infections due to colistin-resistant carbapenem-resistant Enterobacteriaceae (Co-CRE) as well as the factors associated with acquisition of co-CRE. Methods: We conducted a retrospective cross-sectional study from January 2013 till December 2017 on patients admitted to a tertiary care hospital in Karachi, Pakistan. Statistical analysis was done using SPSS 19. Results: Forty patients with Co-CRE were identified of which 29 (72.5%) were males. Median age was 54.5 years. The most common organism isolated was Klebsiella in 22 (55%) followed by Providencia in 5 (12.5%) patients. Most common source of infection was the lung in 12 (30%) followed by urine in 11 (27.5%) patients. Similarly, the most common cause of bacteremia was pneumonia followed by intra-abdominal infections (50% and 37.5% of bacteremia cases, respectively). Twenty-eight (70%) patients had prior cultures with multi-drug-resistant organisms and 36 (90%) had used antibiotics in the past. A quarter (10) patients had pan resistant co-CRE strains while of the remaining strains 66% were sensitive to Fosfomycin. All patients received Colistin-based regimen in combination with 2 or 3 of the following: carbapenem, Fosfomycin, Amikacin, co-triamoxazole, and tigecycline. Complete clinical cure was achieved in only 50% of patients whereas microbiological eradication was achieved in 75%. Higher PITT bacteremia score, solid-organ transplant, and acute kidney injury were associated with mortality in patients with co-CRE. Conclusion: Infections with co-CRE was seen in patients with prior nosocomial exposures and led to poor outcomes, despite combination treatment guided by susceptibilities. Disclosures: All authors: No reported disclosures.